2013
DOI: 10.1364/boe.4.002945
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different metrics for analysis and visualization in spectroscopic optical coherence tomography

Abstract: Spectroscopic Optical Coherence Tomography (S-OCT) extracts depth resolved spectra that are inherently available from OCT signals. The back scattered spectra contain useful functional information regarding the sample, since the light is altered by wavelength dependent absorption and scattering caused by chromophores and structures of the sample. Two aspects dominate the performance of S-OCT: (1) the spectral analysis processing method used to obtain the spatially-resolved spectroscopic information and (2) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Afterwards Principal Component Analysis was employed for feature reduction. The first five principal components were taken for k-means clustering [14]. After the data points were grouped to one of the five clusters, a color map was generated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards Principal Component Analysis was employed for feature reduction. The first five principal components were taken for k-means clustering [14]. After the data points were grouped to one of the five clusters, a color map was generated.…”
Section: Discussionmentioning
confidence: 99%
“…Here the spectroscopic analysis is performed first with a narrow and then with a broad window and both results are combined by multiplication [11]. The dual window method as well as pattern recognition and machine learning algorithms were used in this study to enhance contrast between different images based on spectroscopic features [12][13] [14]. …”
Section: Introductionmentioning
confidence: 99%
“…A more comprehensive and validated comparison of the time-frequency analysis methods for SOCT and LCS described in this chapter is described in Refs [49][50][51]. Other analysis methods for the visualization of spectroscopic information in SOCT images are compared in Ref [52]. …”
Section: Recent Advances In the Field Of Spectroscopic Low-coherence mentioning
confidence: 99%
“…Variations of the above techniques were adopted in other studies. For example, Oldenburg et al used the autocorrelation width of backscattered spectra, at 80% of the peak value, in order to enhance the contrast of OCT images of macrophages and fibroblasts [21], whereas Kartakoullis et al and Jaedicke et al combined the spectral information with principal component analysis (PCA) and clustering algorithms with the intention of differentiating phantom samples consisting of microspheres with different diameters [23,24]. In addition, Tay et al suggested that the use of multiple bandwidths can improve the sensitivity of scatterer size estimates, demonstrating the technique in spectroscopic OCT images where solutions of 0.5 and 45 μm microspheres could be clearly distinguished [25].…”
Section: Introductionmentioning
confidence: 99%